OPTIMASI PENJADWALAN PRIORITAS PRODUKSI WIP REAL TIME BERBASIS SIMPLE ADDITIVE WEIGHTING DAN QR CODE - Deri Nasrudin; Anita Ratnasari (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Work-In-Progress (WIP) management in the pharmaceutical industry requires accurate control because each lot has a holding time limit that affects product stability. Manual processes may cause scheduling delays, incorrect lot retrieval, and storage area congestion. This study aims to develop a web-based WIP management system that generates real-time production priority recommendations. The system development applies Agile, while priority optimization uses Simple Additive Weighting (SAW) with criteria consisting of remaining holding time, urgency level, drum quantity, waiting time, and room occupancy. The system is equipped with QR Code validation during stock-in and stock-out activities to improve data traceability. The simulation results show that Lot 87511XP obtains the highest score of 0.6800 because it has the most critical remaining holding time, is stored in a high-density room, and has a long waiting time. Black box testing indicates that all main functions operate according to the expected scenarios. The proposed system supports more objective scheduling decisions, accelerates WIP monitoring, and helps mitigate overcapacity and holding time violation risks.